Linguistic and Ontological Measures for Comparing the Inconsistent Parts of Models - Batens, Diderik (Logique et Analyse, 1999)
Adaptive logics depend essentially on measures for the degree of abnormality of models. The linguistic approach to such measures compares the sets of abnormal, e.g., inconsistent wffs verified by the models. The ontological approach compares models in terms of `structural' properties that do not depend on the way in which the language is interpreted in the model. While the linguistic approach has not been questioned up to now, present proposals for an ontological approach are affected by several weaknesses. The present paper argues for the attractiveness of an ontological approach and elaborates on the challenge to adequately define it. The final outcome is rather negative: the only sensible definition attained leads to a logic that does not seem to have any suitable application contexts.